2017
DOI: 10.1038/s41598-017-07963-6
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet-induced acceleration of osteoarthritis is associated with a distinct and sustained plasma metabolite signature

Abstract: Metabolic changes induced by high fat diet (HFD) that contribute to osteoarthritis (OA) are poorly understood. We investigated longitudinal changes to metabolites and their contribution to OA pathogenesis in response to HFD. HFD-fed mice exhibited acceleration of spontaneous age-related and surgically-induced OA compared to lean diet (LD)-fed mice. Using metabolomics, we identified that HFD-fed mice exhibited a distinct and sustained plasma metabolite signature rich in phosphatidylcholines (PC) and lysophospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 50 publications
2
50
0
Order By: Relevance
“…As previously stated, the incidence of osteoarthritis in obese individuals is high [32]. Our findings suggest that LEP methylation might be involved in the pathogenesis of osteoarthritis.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As previously stated, the incidence of osteoarthritis in obese individuals is high [32]. Our findings suggest that LEP methylation might be involved in the pathogenesis of osteoarthritis.…”
Section: Discussionsupporting
confidence: 83%
“…Most studies have demonstrated that serum leptin levels in people with osteoarthritis are high [10,15,32]. In our study, LEP promoter methylation levels were higher in obese individuals with osteoarthritis.…”
Section: Discussionsupporting
confidence: 58%
“…Mooney et al showed that surgically-induced OA mice fed a high-fat diet presented not only higher fasting glucose levels and body weights compared to those of lean OA mice, but also had worse OARSI histological scores and less cartilage thickness [40]. Moreover, a recent report also demonstrated that cartilage deterioration was sustained even after the high-fat diet was withdrawn from the OA mice, and the blood glucose and body weight were restored to the levels in normal diet mice [41]. These findings suggested that an increased weight load is not the sole cause of the severity of OA progression; instead, the lipid/glucose metabolic pathways could also jeopardize cartilage integrity and synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…At each week of the time interval, animals were anesthetized with 2.5% isoflurane 24 hours after injection of the final probe and scanned by IVIS imaging to determine fluorescent binding in the knee joint. The fluorescence from the knee joint was quantified by the Living Image software to calculate the flux radiating omnidirectionally from the ROI and graphed as radiant efficiency ([photons/second/cm 2 /str]/[μW/cm 2 ]). To determine an average ROI from the knee fluorescence, the same area of capture was used for each mouse.…”
Section: Fluorescence Imaging Analysismentioning
confidence: 99%
“…1 OA is a manifestation of obesity, aging, trauma, and mechanical stress. 2,3 It typically appears in weight-bearing joints as focal lesions that progressively deepen until the subchondral bone is exposed. 4,5 Although focal lesions in the cartilage can be repaired, no appropriate treatment has been developed to reverse cartilage degradation.…”
Section: Introductionmentioning
confidence: 99%